2005
DOI: 10.1002/app.21169
|View full text |Cite
|
Sign up to set email alerts
|

Pore and crosslinking structures of cotton cellulose crosslinked with DMDHEU‐maleic acid

Abstract: Two dicarboxylic acids (maleic acid and tartaric acid) were used in conjunction with DMDHEU as the crosslinking agents to treat cotton fabric samples. The treated fabrics then were dyed with direct red 81. The results show that the values of the dye absorption, equilibrium absorption, rate constants, and the pore index of structural diffusion resistance constant for the various crosslinking agents are ranked as DMDHEU-tartaric acid Ͼ DMDHEUmaleic acid Ͼ DMDHEU alone at the same dyeing temperature. The activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Hence, soaking the fabrics in DMF for 1 h at 50 °C has a negative effect on the mechanical properties of the fabrics. In previous reports, the cotton cellulose fabrics were mostly treated for 3 min at 160 °C; however, more recent publications suggest that with increasing temperatures up to 180 °C higher crease angles are obtained . Therefore, the second approach involves the curing of the fabrics at 180 °C for 3 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, soaking the fabrics in DMF for 1 h at 50 °C has a negative effect on the mechanical properties of the fabrics. In previous reports, the cotton cellulose fabrics were mostly treated for 3 min at 160 °C; however, more recent publications suggest that with increasing temperatures up to 180 °C higher crease angles are obtained . Therefore, the second approach involves the curing of the fabrics at 180 °C for 3 min.…”
Section: Resultsmentioning
confidence: 99%
“…In several studies, mostly combinations of ethylene ureas 3 and other crosslinking reagents are used to reduce cost and maintain efficiency of the procedures simultaneously reducing the formaldehyde release to a lowest possible level . Formaldehyde‐free textile finishes involve polycarboxylic acids such as maleic acid, itaconic acid, citric acid, 1,2,3,4‐butanetetracarboxylic acid, or others .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some authors have shown that the physical properties of the finished fabrics were affected by the crosslinking structure of the crosslinking agent in/on the finished fabrics [9][10][11][12][13][14].…”
Section: Trj Trjmentioning
confidence: 99%
“…As the well‐known formalization modification for PVA fiber, sealing or crosslinking the free hydroxyl groups of PVA are the effective ways to elevate the water resistance of PVA fiber . However, the free hydroxyl groups of PVA were thought to participate the adsorption process of PVA/PAO composite chelating fibers, so they are not expected to be largely sealed or crosslinked in the formalization process.…”
Section: Introductionmentioning
confidence: 99%
“…The tetrahydroxyl DMDHEU has strong reactivity with hydroxyls, so it can also be used as the crosslinking agent for PVA. Different from FA, DMDHEU has larger molecular size, so its permeabiliy is weaker than that of FA, and it is more likely to form intermolecular crosslinking in PVA . Moreover, the DMDHEU treatment would increase the hydroxyl and uredio groups in adsorbent, which is beneficial for the adsorption performance of the adsorbents .…”
Section: Introductionmentioning
confidence: 99%